Preparation of the Slovak U20 team for the World Junior Championship - Strbak, M. (Haaga-Helia University of Applied Science, 2020)
This thesis is project-based. The objectives of it give an insight into the preparation of the Slovak national U20 team for the World Junior Championship 2020 in the Czech Republic. The thesis covers the process of preparing the team in the pre-season, in-season and de-scribes the performance at the World junior championship. The thesis consists of a theoretical section, main objectives and stages of the project, and final discussion.